Structures and materials - Taylor, Barbara (London : Franklin Watts, 1991)
Examines the properties of various building materials and shows through simple text and specific do-it-yourself projects how the structure of roofs, foundations, and bridges relate to that of the human body.
Includes index.
Keywords: Strength of materials -- Juvenile literature; Strength of materials